FRAGMEN PERADABAN ISLAM DALAM POTRET HISTORIS PERIODESASI TEOLOGI ISLAM (TAJDID: Jurnal Ilmu Ushuluddin, 2019)
The following article understands theology in the pragmen of the history of Islamic civilization by mapping the periodization of the systematic development of Islamic theology from time to time. The discussion of this paper is therefore carried out in a simplistic picture of the history of Islamic theology within the limits of the period, which was carried out to avoid a long historical discussion. This paper then maps the period of development of Islamic theology in three major periods, namely: the classical period, the medieval period, and the modern period. All periods will be systematically elaborated in a systematic and regular nature of historical decisions. This work should be judged by prioritizing the discussion of Islamic theology in the perspective of historical thought which is full of social, political and cultural implications.Tulisan berikut memahami teologi dalam pragmen sejarah peradaban Islam dengan memetakan periodesasi perkembangan sistematis teologi Islam dari masa ke masa. Pembahasan tulisan ini karenanya dilakukan dalam  gambaran simplistis terhadap sejarah teologi Islam dalam batasan periode, yang dilakukan untuk menghindari pembahasan sejarah yang panjang. Tulisan ini selanjutnya memetakan periodesasi perkembangan teologi Islam dalam tiga periode besar, yaitu: periode klasik, periode abad pertengahan, dan periode modern. Semua periode akan dijabarkan secara sistematis dalam kekhasan penutusan sejarah yang bersifat sistematis dan teratur. Karya ini kiranya patut ditilik dengan mengedepankan bahasan teologi Islam dalam perspektif pemikiran sejarah yang sarat dengan iplikasi sosial, politik dan budaya.